Transformation of Education Planning in Indonesia: A Qualitative Review of Documentation and Policy - Khunaifi, Mohammad Aang; Sumarsono, Raden Bambang (Universitas Negeri Malang, 2024)
This research aims to analyze the transformation of education planning in Indonesia through a qualitative review of existing documents and policies. Using a qualitative-interpretive method and literature study, this research analyzes the developments, challenges, and opportunities in education planning in Indonesia. The main focus of this research lies in the paradigm shift, implementation strategies, and the impact of education policies on the national education system. Data was collected through content analysis, including bibliographic annotations and literature reviews. The results show a significant shift in the approach to education planning in Indonesia, from a centralized model to decentralization and participatory approaches. Identified challenges include quality disparities between regions, mismatches between educational outputs and labor market needs, and suboptimal utilization of technology in education. This research provides a comprehensive understanding of the dynamics of education planning in Indonesia and offers recommendations for improving education policies in the future